Design and fabrication of smart rack gadget - Nagantheram, Sigithasan (2011)
The objective of this thesis is to design and fabricate a smart rack gadget for the use of wiremen that is portable and multifunction as well. This smart rack gadget is multifunctional as it possesses extra features such as a removable small tool box and extension plugs. The smart rack gadget can be used to store tools and equipment which used by wiremen such as test pen, wire stripper, Phillips screwdriver and so on. The smart rack gadget can uphold a maximum load of 25 Kg. The material selected for fabrication process is Galvanized iron sheets as it is cheap and easy to be fabricated. Other materials that are used in fabricating this smart rack gadget are handle, lock, and door slot, fasteners such as screws and rivets. The process have been involved in this project are cutting, bending, drilling, welding, riveting, and finishing. Solidwork Simulation Xpress software is used to simulate the stress analysis which occurs at critical part of the smart rack gadget such as the handle. Friction analysis is carried out to find the friction force that occurs at the trolley. Lastly, the objective of the project is achieved since the new smart rack gadget is portable and multifunction as well. It would ease the work of wiremen during their working hours.